IMPACT OF RADIATION FROM WIRELESS COMMUNICATION DEVICE ON HUMAN (International Journal of Engineering Sciences & Management Research, 2014)
As the time changes, so the communication mode is also. With the fast growth in technology wireless communication becomes more dominated in comparison to wired communication. But due to this, human living organisms are increasingly exposed to microwave / radio frequency (RF) radiation from wireless communication technology including the mobile phones and base stations. So the objective of this paper is to summarise the effects of RF radiation, factors affecting the body exposure and remedies to avoid harmful effects.